High-speed efforts of elite association football referees in national and international matches - Amatori, S.; Helsen, W. F.; Baldari, C.; Serra, T.; Belli, A.; Guidetti, L.; Rocchi, M. B. L.; Sisti, D.; Perroni, F. (The Journal of Strength and Conditioning Research, 2024)
Field referees (FRs) need to move throughout the pitch to identify any infringements of the game's laws. Their performance depends on technical, tactical, physical, physiological, and mental factors. This retrospective study aimed to examine and assess the physical and physiological parameters as a function of time in elite association football referees during official matches. Global positioning system (match time, distance in different intensity ranges [low-intensity, high-speed, very high-speed running, and sprinting], average and peak speed, distance in accelerations or decelerations) and heart rate (average and peak) data from 212 national and international football matches were analyzed. A linear mixed-model analysis was performed to assess the differences between halves and between the three 15-minute sections of each half-time for all the physical and physiological variables collected. A significant effect of match half was found for the game time (p < 0.001) and the standing time (p = 0.005), both higher in the second half, and for the average speed (p = 0.017), which was lower in the second half. Total distance (p < 0.001), low-intensity distance (p = 0.004), and average speed (p = 0.007) all showed a reduction as a function of time. More than 7.800 high-speed intervals were detected. Accelerative actions within 3 seconds characterized most of the high-speed efforts of an FR during a match. Significant differences emerged in the way the match intensity is distributed across the match, analyzed both in halves (first vs. second) and 15-minute intervals within each half. It is important to emphasize the importance of high-speed training with a focus on a faster transition from low- to high-speed running to keep up with the play to get into an appropriate position and subsequently make the correct decisions.